Three-Dimensional Measurements of Sphenoid Sinus Size by Sex in a Korean Population: An Exploratory Study - Jeong-Hyun Lee; Jong-Tae Park (Diagnostics, 2024)
Background/Objectives: This study aims to investigate the three-dimensional morphological differences of the sphenoid sinus according to sex in the Korean adult population and conduct an exploratory study based on the findings. The sphenoid sinus, located deep within the skull, plays a crucial role in forensic identification due to its relative protection from external damage and its unique anatomical characteristics. Methods: Using cone-beam computed tomography (CBCT) data from 120 patients (60 males and 60 females) aged 20–29, the sphenoid sinus was visualized and measured in three dimensions using Mimics software (version 22.0). Measurements included the volume of the sphenoid sinus, as well as its dimensions in the X, Y, and Z axes. The measured data were analyzed using SPSS (version 23.0) with a t-test and linear regression analysis. Results: The results showed that the sphenoid sinus volume was significantly larger in males compared to females (p < 0.05), with an average male sinus volume of 16,957.9 mm3 and a female volume of 13,517.7 mm3. Additionally, the X-width, Y-width, and Z-width were all larger in males, with significant differences (p < 0.001) across all dimensions. Further regression analysis revealed that the volume of the sphenoid sinus was primarily influenced by the Z-axis height (measured from the coronal view) and the Y-axis width (measured from the sagittal view), while the X-axis width had a negligible effect on the overall volume. Conclusions: These findings suggest that sex-specific differences in the sphenoid sinus may provide important insights for clinical diagnoses and forensic personal identification. This study highlights the need for further research on different age groups and ethnic populations to enhance the understanding of anatomical variations in the sphenoid sinus and their potential applications in both medical and forensic fields.